Evaluierung medizinischer Volumenrendering-Algorithmen durch empirische Studien - Domik, Gitta; Arens, Stephan; Tünnermann, Jan; Scharlau, Ingrid (FIfF-Kommunikation)
Wie gut ist ein Rendering Algorithmus, der Bilder aus Daten generiert, die wiederum als Grundlage für eine medizinische Diagnose verwendet werden? In diesem Beitrag werden einerseits beispielhaft empirische Studien und ihre Ergebnisse vorgestellt, die solche Fragestellungen beantworten. Andererseits widmen wir uns auch der generellen Frage, welche Herausforderungen gemeistert werden müssen, um empirische Studien aufzustellen, die in Bezug auf korrekte medizinische Diagnosen und ihre zugrunde liegenden Rendering-Algorithmen sinnvoll sind.
Keywords: Informatik; Visualisierung; Psychologie; Experimentaldesign

Praxis nach Rezept? – Praxisbezug und Professionalität in den subjektiven Theorien von Lehramtsstudierenden - Schüssler, Renate; Keuffer, Josef; Günnewig, Kathrin; Scharlau, Ingrid (Reform der Lehrerbildung in Deutschland, Österreich und der Schweiz. Teil I: Analyse, Perspektiven und Forschung)

Wie sehen Studierende das Verhältnis von Studium und Beruf? Praxisbezug und Professionalität in den Subjektiven Theorien Studierender - Oechsle, Mechthild; Scharlau, Ingrid; Hessler, Gudrun; Günnewig, Kathrin (Der Bologna-Prozess aus Sicht der Hochschulforschung)
Der Beitrag befasst sich mit der Frage, auf welche Weise Studierende die Anforderungen von Wissenschaft und Berufspraxis aufeinander beziehen und welche Subjektiven Theorien sie hierzu entwickeln. Basierend auf einer qualitativen Befragung von Studierenden des Lehramts und der Soziologie rekonstruiert der Beitrag verschiedene Konzepte von Praxisbezug und Professionalität und analysiert mögliche Zusammenhänge zwischen diesen Konzepten. Der Beitrag macht deutlich, dass es neben der (erwartbaren) Heterogenität zwischen den Studiengängen eine erhebliche Heterogenität der entsprechenden Subjektiven Theorien innerhalb der jeweiligen Studiengänge gibt und diskutiert mögliche Schlussfolgerungen für die universitäre Lehre.

Self-Assessment-Instrumente: Eine Möglichkeit der Reflexion und Differenzierung von Subjektiven Theorien - Scharlau, Ingrid (Workshop: Zum Verhältnis von Studium und Berufspraxis. Perspektiven von Lehrenden und Studierenden)

Top-down contingent feature-specific orienting with and without awareness of the visual input. - Ansorge, Ulrich; Horstmann, Gernot; Scharlau, Ingrid (Advances in Cognitive Psychology)
In the present article, the role of endogenous feature-specific orienting for conscious and unconscious vision is reviewed. We start with an overview of orienting. We proceed with a review of masking research, and the definition of the criteria of experimental protocols that demonstrate endogenous and exogenous orienting, respectively. Against this background of criteria, we assess studies of unconscious orienting and come to the conclusion that so far studies of unconscious orienting demonstrated endogenous feature-specific orienting. The review closes with a discussion of the role of unconscious orienting in action control. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: visual input; awareness; conscious; orientation; visual perception; Awareness; Consciousness States; Perceptual Orientation; Visual Perception; Blindsight

Prior entry explains order reversals in the attentional blink. - Olivers, Christian N. L.; Hilkenmeier, Frederic; Scharlau, Ingrid (Attention, Perception, & Psychophysics)
When two targets are presented in rapid succession, the first target (T1) is usually identified, but the second target (T2) is often missed. A remarkable exception to this 'attentional blink' occurs when T2 immediately follows the first T1, at lag 1. It is then often spared but reported in the wrong order—that is, before T1. These order reversals have led to the hypothesis that 'lag 1 sparing' occurs because the two targets merge into a single episodic representation. Here, we report evidence consistent with an alternative theory: T2 receives more attention than T1, leading to prior entry into working memory. Two experiments showed that the more T2 performance exceeded that for T1, the more order reversals were made. Furthermore, precuing T1 led to a shift in performance benefits from T2 to T1 and to an equivalent reduction in order reversals. We conclude that it is not necessary to assume episodic integration to explain lag 1 sparing or the accompanying order reversals. (PsycINFO Dat
Keywords: attentional blink; order reversals; prior entry; working memory; visual attention; attentional performance; Adolescent; Adult; Attention; Attentional Blink; Color Perception; Cues; Discrimination (Psychology); Female; Humans; Male; Memory; Short-Term; Pattern Recognition; Visual; Psychophysics; Reaction Time; Reversal Learning; Sensory Gating; Serial Learning; Young Adult; Eyeblink Reflex; Stimulus Change; Stimulus Parameters; Visual Attention; Attentional Blink; Short Term Memory

Simultaneity and temporal order perception: Different sides of the same coin? Evidence from a visual prior-entry study. - Weiß, Katharina; Scharlau, Ingrid (The Quarterly Journal of Experimental Psychology)
Attended stimuli are perceived as occurring earlier than unattended stimuli. This phenomenon of prior entry is usually identified by a shift in the point of subjective simultaneity (PSS) in temporal order judgements (TOJs). According to its traditional psychophysical interpretation, the PSS coincides with the perception of simultaneity. This assumption is, however, questionable. Technically, the PSS represents the temporal interval between two stimuli at which the two alternative TOJs are equally likely. Thus it also seems possible that observers perceive not simultaneity, but uncertainty of temporal order. This possibility is supported by prior-entry studies, which find that perception of simultaneity is not very likely at the PSS. The present study tested the percept at the PSS in prior entry, using peripheral cues to orient attention. We found that manipulating attention caused varying temporal perceptions around the PSS. On some occasions observers perceived the two stimuli as sim
Keywords: temporal order perception; simultaneity; temporal order judgment; attention; visual perception; Adolescent; Adult; Attention; Cues; Discrimination (Psychology); Female; Humans; Judgment; Male; Models; Psychological; Photic Stimulation; Reaction Time; Time Factors; Uncertainty; Visual Perception; Young Adult; Attention; Judgment; Stimulus Similarity; Time Perception; Visual Discrimination; Temporal Order (Judgment)

Enhancing implicit change detection through action. - Tseng, Philip; Tuennermann, Jan; Roker-Knight, Nancy; Winter, Dorina; Scharlau, Ingrid; Bridgeman, Bruce (Perception)
Implicit change detection demonstrates how the visual system can benefit from stored information that is not immediately available to conscious awareness. We investigated the role of motor action in this context. In the first two experiments, using a one-shot implicit change detection paradigm, participants responded to unperceived changes either with an action (jabbing the screen at the guessed location of a change) or with words (verbal report), and sat either 60 cm or 300 cm (with a laser pointer) away from the display. Our observers guessed the locations of changes at a reachable distance better with an action than with a verbal judgment. At 300 cm, beyond reach, the motor advantage disappeared. In experiment 3, this advantage was also unavailable when participants sat at a reachable distance but responded with hand-held laser pointers near their bodies. We conclude that a motor system specialized for real-time visually guided behavior has access to additional visual information.
Keywords: implicit change detection; action perception; visual system; perceptual judgment; verbal fluency; Analysis of Variance; Awareness; Female; Humans; Male; Psychomotor Performance; Random Allocation; Reaction Time; Visual Perception; Visual Memory; Visual Stimulation; Implicit Memory; Judgment; Perceptual Discrimination

Temporal order judgments: A sensitive measure for measuring perceptual latency? - Weiß, Katharina; Scharlau, Ingrid (Proceedings of the 26th Annual Meeting of the International Society for Psychophysics)
Temporal order judgments (TOJs) have been used for demonstrating the facilitating effect of attention on information processing - prior entry. Prior entry is a robust, often large effect. Besides attention, other factors shorten perceptual latency, for instance stimulus saliency, action affordances of an object, or threatening objects. The expectable size for these effects is far smaller than that usually obtained for prior entry. Some effects might consist of only a few milliseconds. But are TOJs sensitive enough for detecting such small effects? For answering this question, we tested whether objects highly associated with a certain color are perceived earlier. In a four-alternative TOJ, including a "simultaneous" and "uncertain" category, we found a small advantage for high color diagnostic objects. This indicates high sensitivity of the TOJ task. We also found that "simultaneous" judgements were most sensitive. This is important for the debate on the usefulness of order vs. simultaneous judgments.

Top–down contingent attentional capture during feed-forward visual processing. - Ansorge, Ulrich; Horstmann, Gernot; Scharlau, Ingrid (Acta Psychologica)
Comments on an article by Jan Theeuwes (see record [rid]2010-20897-002[/rid]). Theeuwes summarizes an impressive number of studies demonstrating interference by irrelevant visual singletons in computer experiments with humans. Theeuwes assumes that this salience-driven capture of attention is fast and occurs within 150 ms since singleton onset, during the feed-forward phase of visual processing. In contrast to Theeuwes, we think that top–down contingent capture is the rule and explains initial and fast attention capture effects in the first feed-forward phase of visual processing. During a later phase and under some conditions exogenous capture of attention possibly follows. At the same time, we propose that the evidence presented by Theeuwes fails to support exogenous orienting because it fails to exclude a top–down contingent capture explanation. We present our arguments in two sections. One major source of evidence for top–down controlled attentional capture during the feed-forward
Keywords: visual selection; attention; information; visual field; brain; Attention; Humans; Models; Psychological; Visual Perception; Volition; Brain; Visual Field; Visual Perception; Visual Attention; Information

Rapid allocation of temporal attention in the attentional blink paradigm. - Hilkenmeier, Frederic; Scharlau, Ingrid (European Journal of Cognitive Psychology)
How fast can information of a first target (T1) in a rapid serial visual presentation be used for top-down allocation of attention in time? A valid cue about the temporal position of a second target (T2) was integrated into T1. The data show that 100 ms after T1 onset, T2 was identified better than without cue, raising the conditional T2 performance. T1 apparently triggers a facilitative effect of attention, known from other paradigms such as peripheral cueing. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: temporal attention; attentional blink paradigm; first target information; top-down allocation; rapid serial visual presentation; Stimulus Presentation Methods; Visual Stimulation; Visual Attention

Jean Piaget, Die Entwicklung der physikalischen Mengenbegriffe beim Kinde: Erhaltung und Atomismus - Scharlau, Ingrid; Aebli, Hans (Kindlers Literatur Lexikon)

Jean Piaget, Das Erwachen der Intelligenz beim Kinde - Scharlau, Ingrid; Aebli, Hans (Kindlers Literatur Lexikon)

Early Top-Down Influences in Control of Attention: Evidence from the Attentional Blink - Hilkenmeier, Frederic; Tünnermann, Jan; Scharlau, Ingrid (KI 2009: Advances in Artificial Intelligence. Proceedings of the 32nd Annual Conference on Artificial Intelligence.)
The relevance of top-down information in the deployment of attention has more and more been emphasized in cognitive psychology. We present recent findings about the dynamic of these processes and also demonstrate that task relevance can be adjusted rapidly by incoming bottom-up information. This adjustment substantially increases performance in a subsequent task. Implications for artificial visual models are discussed.
Keywords: visuo-spatial attention; top-down control; task relevance; artificial visual attention; attentional blink

Attention Speeds Up Visual Information Processing: Selection for Perception or Selection for Action? - Weiß, Katharina; Scharlau, Ingrid (KI 2009: Advances in Artificial Intelligence. Proceedings of the 32nd Annual Conference on Artificial Intelligence.)
Attention speeds up information processing. Although this finding has a long history in experimental psychology, it has found less regard in computational models of visual attention. In psychological research, two frameworks explain the function of attention.Selection for perception emphasizes that perception- or consciousness-related processing presupposes selection of relevant information, whereas selection for action emphasizes that action constraints make selection necessary. In the present study, we ask whether or how far attention, as measured by the speed-up of information processing, is based on selection for perception or selection for action. The accelerating effect was primarily based on selection for perception, but there was also a substantial effect of selection for action.
Keywords: visuo-spatial attention; prior entry; selection for action; selection for perception

What you see is what you set – the position of moving objects - Priess, Heinz-Werner; Scharlau, Ingrid (KI 2009: Advances in Artificial Intelligence. Proceedings of the 32nd Annual Conference on Artificial Intelligence.)
Human observers consequently misjudge the position of moving objects towards the direction of motion. This so called flash-lag effect is supposed to be related to very basic processes such as processing latencies in the human brain. In our study we show that this effect can be inversed by changing the task-set of the observer. A top-down change of the observers attentional set leads to a different perception of otherwise identical scenes. Cognitive theories regard the misperception of the moving object as an important feature of attention-mediated processing, because it reflects the prioritized processing of important objects.

Jean Piaget zur Einführung - Scharlau, Ingrid

Control of Attention by Nonconscious Information: Do Intentions Play a Role? - Scharlau, Ingrid (The 5th International Conference on Computer Vision Systems)
The present study explores the deployment of attention towards nonconscious information. It is both theoretically and empirically likely that the deployment of attention can be controlled by information which is not consciously registered (attentional priming), similar to the control of sensorimotor responses by nonconscious information (response priming). However, not much is known about the functional basis of attentional priming. The present experiment explore whether and how strongly intentions (current action pans) determine whether attention is allocated towards invisible information (so called direct parameter specification). The results demonstrate that intention-mediated control is possible, but it seems to break down easily, that is to provide a weak and non-robust type of control.
Keywords: visuo-spatial attention; metacontrast; masking; intention; direct parameter specification; perceptual latency; priming

Temporal processes in prime-mask interaction: Assessing perceptual consequences of masked information. - Scharlau, Ingrid (Advances in Cognitive Psychology)
Visual backward masking is frequently used to study the temporal dynamics of visual perception. These dynamics may include the temporal features of conscious percepts, as suggested, for instance, by the asynchronous-updating model (Neumann, 1982) and perceptual-retouch theory (Bachmann, 1994). These models predict that the perceptual latency of a visual backward mask is shorter than that of a like reference stimulus that was not preceded by a masked stimulus. The prediction has been confirmed by studies using temporal-order judgments: For certain asynchronies between mask and reference stimulus, temporal-order reversals are quite frequent (e.g. Scharlau, & Neumann, 2003a). However, it may be argued that these reversals were due to a response bias in favour of the mask rather than true temporal-perceptual effects. I introduce two measures for assessing latency effects that (1) are not prone to such a response bias, (2) allow to quantify the latency gain, and (3) extend the perceptual e
Keywords: temporal processes; prime mask interaction; perceptual consequences; masked information; visual backward masking; visual perception; Temporal Lobe; Visual Masking; Visual Perception; Consequence

Experiments on the Fehrer-Raab effect and the 'Weather Station Model' of visual backward masking. - Neumann, Odmar; Scharlau, Ingrid (Psychological Research)
The Fehrer-Raab effect (simple reaction time is unaffected by metacontrast masking of the test stimulus) seems to imply that a stimulus can trigger a voluntary reaction without reaching a conscious representation. However, it is also possible that the mask triggers the reaction, and that the masked test stimulus causes a focussing of attention from which processing of the mask profits, thus reaching conscious representation earlier. This is predicted by the Weather Station Model of visual masking. Three experiments tested this explanation. Experiment 1 showed that the masked test stimulus caused a temporal shift of the mask. Experiment 2 showed that the reaction in the Fehrer-Raab effect was not exclusively triggered by a conscious representation of the test stimulus: the mask was involved in evoking the reaction. Experiment 3 again revealed a temporal shift of the mask. However, the shift was only about half as large as the Fehrer-Raab effect. The psychometric functions suggested tha
Keywords: Fehrer-Raab effect; Weather Station Model; visual backward masking; reaction time; metacontrast masking; conscious representation; Cognition; Humans; Perceptual Masking; Pilot Projects; Psychology; Experimental; Psychometrics; Reaction Time; Visual Perception; Models; Reaction Time; Visual Contrast; Visual Masking